Assessing the impact of microwave treatment on the nutritional quality and metabolomic profile of barley flour - Mavuri Tejaswini Durga; Alonkrita Chowdhury; Rajesh Kumar; S. Suvetha; Dodla Mamatha; Akshita Trivedi; Kratika Maurya; Pavan Kumar Yadav; Mayukh Ghosh (Journal of Agriculture and Food Research, 2025)
Microwave treatment effectively enhances barley's functional food properties while reducing anti-nutritional factors (ANFs) such as phytates, trypsin inhibitors, and condensed tannins, which limit nutrient bioavailability. Conventional thermal methods reduce ANFs but degrade bioactive compounds. Microwave processing offers an alternative, preserving or enhancing these components. This study evaluated microwave treatments (300–800 W, 1.5–9 min) effects on barley flour compared to untreated samples. Favorable treatments, T-4, T-5, T-6 (600 W, 2, 4, and 6 min), and T-7 (800 W, 1.5 min), increased total phenolic content from 1622.98 μg GAE/g DW (control) to 1890.43 μg GAE/g DW (T-4). Antioxidant activities were enhanced, including DPPH scavenging (2046.11 μg AAE/g DW, T-7), ABTS scavenging (1271.55 μg GAE/g DW, T-6), total antioxidant capacity (4397.14 μg AAE/g DW, T-7), FRAP (1920.80 μg AAE/g DW, T-7), CUPRAC (4278.10 μg AAE/g DW, T-5), and ferrous ion chelation (256.47 μg EDTA eq./g DW, T-6). ANFs, such as phytates (516.83 μg PAE/g DW in T-4), trypsin inhibitors (0.11 mg/g DW in T-6), and condensed tannins (194.23 μg CE/g DW in T-1), were reduced in treatment-specific manner. LC-HRMS-based metabolomics revealed T-7 as the most effective treatment, enhancing various phenolics and flavonoids (e.g., ferulic acid, catechin) while maintaining sugars, lipids, and vitamins. Multivariate analyses confirmed T-7's superiority in preserving metabolite integrity while improving nutritional and functional properties. Excessive power and prolonged exposure (e.g., T-9: 800 W, 5 min) led to the degradation of bioactive compounds. This study highlights microwave processing as a sustainable and effective approach for developing functional foods from barley.